2017
DOI: 10.3390/su9020223
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Pressurized Gas in Low Air-Conductivity Coal Seam Using Drainage Roadway

Abstract: Abstract:A drainage roadway was constructed in the fractured zone beside an air-return roadway of a mining site. However, drainage roadways serve only one working face and are discarded after mining, thus weakening sustainable mining practices. To improve the sustainability at mining sites, this paper proposes a new drainage roadway that can serve two adjacent working faces. A schematic layout of the proposed lateral high drainage roadway (LHDR) is presented. The LHDR can be used to extract pressurized gas fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Former research has shown that a rock drainage roadway and high-level directional extraction borehole can effectively extract gas in the fissure zone and have great operational stability in the upper corner of the goaf and return air flow [10][11][12][13]. However, the rock drainage roadway has the disadvantage of requiring a large amount of site construction, long operation cycles, and high costs [14][15][16]. With improved equipment, the high-level directional extraction borehole can replace the high-level drainage roadway to extract gas in the goaf and fissure cycles, and high costs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Former research has shown that a rock drainage roadway and high-level directional extraction borehole can effectively extract gas in the fissure zone and have great operational stability in the upper corner of the goaf and return air flow [10][11][12][13]. However, the rock drainage roadway has the disadvantage of requiring a large amount of site construction, long operation cycles, and high costs [14][15][16]. With improved equipment, the high-level directional extraction borehole can replace the high-level drainage roadway to extract gas in the goaf and fissure cycles, and high costs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars studied the gas extraction method (e.g., high-level boreholes extraction and high drainage roadway extraction) in the mine-out areas after mining [22,23]. Among them, high-level boreholes extraction is an efficient gas extraction method to control gas over the limit.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research results of the distribution and evolution characteristics of the floor rock layer in the upper coal seam working face are mainly based on the finite element numerical calculation and similar material simulation experiments and lack of theoretical research on the floor rock mass movement. At the same time, the floor stress field monitoring research has the characteristics of difficult testing and high cost, and the research progress is slow [15][16][17][18][19][20]. In addition, a large number of domestic and foreign scholars have made a lot of research results on the influence of floor level and gas layer [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%